2018
DOI: 10.3390/nano8040269
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Glycerol Oxidation over Plasmonic Au and AuM (M = Pt, Pd and Bi) Nanoparticle-Decorated TiO2 Photocatalysts

Abstract: In this study, sol-immobilization was used to prepare gold nanoparticle (Au NP)-decorated titanium dioxide (TiO2) photocatalysts at different Au weight % (wt. %) loading (Aux/TiO2, where x is the Au wt. %) and Au–M NP-decorated TiO2 photocatalysts (Au3M3/TiO2), where M is bismuth (Bi), platinum (Pt) or palladium (Pd) at 3 wt. %. The Aux/TiO2 photocatalysts exhibited a stronger visible light absorption than the parent TiO2 due to the localized surface plasmon resonance effect. Increasing the Au content from 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Five binding energy ranges corresponding to the Ti 2p, O 1s, C 1s, N 1s, and Si 2p orbitals are presented. The two binding energies of 459.4 and 465.1 eV are assignable to Ti 2p 3/2 and 2p 1/2 orbital electrons, respectively, bonded to oxygen (Ti–O) [29,30]. The two binding energies of 528.4 and 531.0 eV can be assigned to the O 1s orbital electrons linked to titanium (O–Ti) and hydrogen (O–H) in the hydroxy group, respectively [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Five binding energy ranges corresponding to the Ti 2p, O 1s, C 1s, N 1s, and Si 2p orbitals are presented. The two binding energies of 459.4 and 465.1 eV are assignable to Ti 2p 3/2 and 2p 1/2 orbital electrons, respectively, bonded to oxygen (Ti–O) [29,30]. The two binding energies of 528.4 and 531.0 eV can be assigned to the O 1s orbital electrons linked to titanium (O–Ti) and hydrogen (O–H) in the hydroxy group, respectively [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…It must also be noted that the LSPR resonance observed by Bian et al [ 254 ] was quite broad—implying a low Q-factor for the resonance, and the resulting weak local field amplification factor might have also contributed to the low quantum yields obtained. Hunsom et al obtained a tripling in the rate of photoinduced glycerol oxidation by using Au NP-decorated TiO 2 photocatalysts instead of bare TiO 2 [ 255 ]. Further improvements in catalytic activity for glycerol photo-oxidation were achieved using bimetallic AuPd, AuPt, and AuBi NP/TiO 2 heterojunctions with AuPd/TiO 2 producing the highest performance which was attributed to optimal light harvesting and efficient charge separation [ 255 ].…”
Section: Exploiting Hot Electronsmentioning
confidence: 99%
“…Hunsom et al obtained a tripling in the rate of photoinduced glycerol oxidation by using Au NP-decorated TiO 2 photocatalysts instead of bare TiO 2 [ 255 ]. Further improvements in catalytic activity for glycerol photo-oxidation were achieved using bimetallic AuPd, AuPt, and AuBi NP/TiO 2 heterojunctions with AuPd/TiO 2 producing the highest performance which was attributed to optimal light harvesting and efficient charge separation [ 255 ].…”
Section: Exploiting Hot Electronsmentioning
confidence: 99%
“…In most cases, it is found that noble metal nanoparticles (NPs) play an essential role in promoting the dissociation of polyols, which served as an electron donor in hydrogen production or as an reactant in chemical synthesis. Several research groups have tried to unravel the promotional mechanisms of metal NPs and proposed that the enhanced charge storage and transfer kinetics account for the enhanced catalytic performance. In addition, some metal NPs extend the light absorption of the photocatalysts into the visible light region owing to their plasmonic effect, which also benefits the polyol conversion to some extent. Mechanisms of catalytic polyol dissociation have also been proposed on the basis of global kinetics. Lercher and co-authors have studied the photoreforming of ethylene glycol using both Rh/TiO 2 and Rh/GaN/ZnO photocatalysts .…”
Section: Introductionmentioning
confidence: 99%